S.A.E. handbook. - Society of Automotive Engineers (Warrendale, Pa. Society of Automotive Engineers, 1993)
Annual, 1928- Semiannual, -1927
v.1 Materials -- v.2 Parts and components -- v.3 Engines, fuels, lubricants, emissions, and noise -- v.4 On-highway vehicles and off-highway machinery.
A supplement to the 1933 edition, issued August 1934, takes the place of the regular 1934 issue.
Annual
Earlier data sheets were published by the society in loose-leaf form under cover-title: Standards and data sheets. [New York, 1917] 2 v.
Two supplements to the 1931 edition, issued 1931 and January 1932, and loose-leaf sheets including additions adopted in June 1932, take the place of the regular 1932 issue.
Keywords: Automobiles -- Handbooks, manuals, etc